Banking Accounting Practices “Humanist” - Shonhadji, Nanang (International Research Journal of Business Studies, 2016)
Humanism is a universal value that should be attached to all forms and operational activities of the bank because the bank’s main business is to provide service to humanity. The purpose of this study was to determine the humanist banking practice. The use of qualitative methods with a phenomenological approach that involve an account officer and marketing staff as key informants. In-depth interviews conducted to obtain comprehensive information. The results of the study informs that the banking practice in the lending and the funding activities were still oriented to material interests or to achieve maximum profit with unbalanced position. It caused the values of humanism in the form of truth and equitable negated by bank stakeholder. The results of this study also found that there are two forms of awareness is needed in the value of accountability in the process of funding and lending activities to customers humanistic were the awareness of responsibility to themselves and to God.